The impact of mindfulness-based stress reduction on psychological health among patients with chronic diseases during COVID-19 outbreak lockdown - Hasnaa Osama; Hoda M. Rabea; Mona A. Abdelrahman (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background The emergence of COVID-19 has spurred a wide range of psychological morbidities. However, its influence on a vulnerable population with chronic conditions is less addressed. Therefore, this study aimed to investigate the psychological health among patients with chronic diseases during the elevated psychiatric distress associated with the outbreak and examine the efficacy and feasibility of mindfulness-based stress reduction intervention (MBSR). The study involved 149 participants recruited from university hospital outpatient clinics. Patients were allocated into two groups: MBSR training program and control group. Standardized questionnaires were administered to assess depression, anxiety and stress prior to the MBSR program and at completion of the training after 8 weeks. Results The results showed that MBSR intervention improved psychological distress and decreased the mean scores of depression, anxiety and stress. Conclusions Mindfulness training program based on audio and smartphone was feasible and effective when it was applied to patients with chronic diseases and showed positive impact on negative psychological stress domains. These findings pave the way for the integration of psychological support for patients with chronic illnesses in clinical settings.